piggyBac Transposition and the Expression of Human Cystatin C in Transgenic Chickens - Seo Woo Kim; Jeong Hyo Lee; Ji Seon Han; Seung Pyo Shin; Tae Sub Park (Animals, 2021)
A bioreactor can be used for mass production of therapeutic proteins and other bioactive substances. Although various methods have been developed using microorganisms and animal cells, advanced strategies are needed for the efficient production of biofunctional proteins. In microorganisms, post-translational glycosylation and modification are not performed properly, while animal cell systems require more time and expense. To overcome these problems, new methods using products from transgenic animals have been considered, such as genetically modified cow’s milk and hen’s eggs. In this study, based on a non-viral piggyBac transposition system, we generated transgenic bioreactor chickens that produced human cystatin C (hCST3). There were no differences in the phenotype or histochemical structure of the wild-type and hCST3-expressing transgenic chickens. Subsequently, we analyzed the hCST3 expression in transgenic chickens, mainly in muscle and egg white, which could be major deposition warehouses for hCST3 protein. In both muscle and egg white, we detected high hCST3 expression by ELISA and Western blotting. hCST3 proteins were efficiently purified from muscle and egg white of transgenic chickens using a His-tag purification system. These data show that transgenic chickens can be efficiently used as a bioreactor for the mass production of bioactive materials.